The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1029/2019jg005206
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Forest Management Stabilizes Carbon Under Projected Climate and Wildfires

Abstract: Forests provide a broad set of ecosystem services, including climate regulation. Other ecosystem services can be ecosystem dependent and are in part regulated by local‐scale decision‐making. In the southwestern United States, ongoing climate change is exacerbating a legacy of fire‐exclusion that has altered forest structure and increased high‐severity wildfire risk. Management can mitigate this risk by reducing forest density and restoring frequent surface fires, but at the cost of reduced carbon stocks. We so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 84 publications
0
44
1
Order By: Relevance
“…Mildrexler et al contains no analysis of changes in carbon stocks over time, despite current and projected increases in climate change-driven drought and wildfire (Halofsky et al, 2020;Parks and Abatzoglou, 2020). Other studies of dry forest ecosystems that incorporate disturbance-mediated mortality conclude that management strategies informed by historical conditions stabilize carbon stocks given projected climate change (Liang et al, 2018;Hurteau et al, 2019;Krofcheck et al, 2019;McCauley et al, 2019).…”
Section: Misrepresenting the Historical Abundance Of Grand Firmentioning
confidence: 99%
See 1 more Smart Citation
“…Mildrexler et al contains no analysis of changes in carbon stocks over time, despite current and projected increases in climate change-driven drought and wildfire (Halofsky et al, 2020;Parks and Abatzoglou, 2020). Other studies of dry forest ecosystems that incorporate disturbance-mediated mortality conclude that management strategies informed by historical conditions stabilize carbon stocks given projected climate change (Liang et al, 2018;Hurteau et al, 2019;Krofcheck et al, 2019;McCauley et al, 2019).…”
Section: Misrepresenting the Historical Abundance Of Grand Firmentioning
confidence: 99%
“…In particular, the number of shade-tolerant fir ≥53 cm DBH increased substantially over the last century as a consequence of fire exclusion (Hagmann et al, 2013(Hagmann et al, , 2014Merschel et al, 2014;Johnston, 2017;Johnston et al, 2018). Mildrexler et al ignore research showing that dry forests have overshot their carbon-carrying capacity and that thinning treatments, although they reduce carbon stocks in the short term, will tend to stabilize carbon stocks over multi-decadal time scales in the face of a warming climate (e.g., Hurteau et al, 2019;Krofcheck et al, 2019). Mildrexler et al assert without evidence that large shade-tolerant fir are not overrepresented on the landscape and that forests of eastern Oregon have "low future climatic vulnerability."…”
Section: Mildrexler Et Al Misrepresent Forest Ecology and Carbon Dynmentioning
confidence: 99%
“…They found that disturbance may drive the range expansion of broad-leaved species, and conifers were favored for pulp production. In addition, other previous studies focused on the effect of, for example, fire and harvesting [17,18], forest carbon management [19], and forest ecosystem services [20]. Forest landscape simulations are helpful for understanding the effect of climate and harvesting on forest AGB, and to formulate corresponding forest management strategies in advance.…”
Section: Introductionmentioning
confidence: 99%
“…Stand T-15 was thinned in 2015. We do not show stand T-17 in the image because the Google maps image was from prior to 2017 and does not show the thinning in T-17. in the short-term, but protect and stabilize long-term storage in live large trees (Krofcheck et al, 2019;Sorensen et al, 2011). There have been fewer studies of respiration and belowground components.…”
mentioning
confidence: 99%
“…Modeling studies suggest that thinning and associated prescribed burning treatments in ponderosa pine forests reduce carbon storage DOUGHTY ET AL. in the short-term, but protect and stabilize long-term storage in live large trees (Krofcheck et al, 2019;Sorensen et al, 2011). There have been fewer studies of respiration and belowground components.…”
mentioning
confidence: 99%